„Ja, jako psycholog, mówię ci…”: ontologiczna narracja uchodźcy opozycyjnego z epoki „Solidarności” - Erdmans, Mary Patrice (Człowiek i Społeczeństwo, 2019)
Using the life story method first introduced in The Polish Peasant, this paper analyzes the life story of a „Solidarity” refugee, positioning the subjective standpoint at the center of analysis and interpreting social action as both agentic and responsive to objective conditions. The ontological narrative in his life story is plotted through a professional schema. He defined the turning points in his life as intentionally driven by his motivation to be an organizational psychologist: his opposition within the communist system; the reason for his internment during martial law; the choice of where to emigrate; and the decision to return to Poland. He constructed a coherent narrative defined by volitional reactions to changing situations. In the life story method, subjective perceptions encode objective conditions allowing us to analyze the interactions between the self and society. Mary Patrice Erdmans, Ja, jako psycholog, mówię ci…”: ontologiczna narracja uchodźcy opozycyjnego z epoki „Solidarności” [„I, a psychologist, tell you”: The Ontological Narrative of a „Solidarity” Refugee] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVII: „Chłop polski w Europie i Ameryce” po stu latach [Polish peasant in Europe and America after one hundred years], Poznań 2019, pp. 119–141, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.